Long Term Interactions of Microorganisms and Prudhoe Bay Crude Oil in Tundra Soils at Barrow, Alaska - Sexstone, Alan; Gustin, Paula; Atlas, Ronald M. (ARCTIC, 1978)
Oil was recovered from tundra soils two and seven years after spillage. Oil persisted in the upper soil layer. The depth of penetration appears to depend on soil moisture and drainage characteristics. Maximal penetration seems to occur within one year of spillage. Biodegradation of the oil was indicated by changes in the ratio of gas chromatographically resolved to unresolved components. Individual components appear to be preferentially degraded, but no evidence was found for significant preferential degradation of structural classes of hydrocarbons. Numbers of microorganisms were different in oil contaminated and reference soils generally showing continued enrichment, but in some soils showing inhibition of microbial populations.